Magnesio-hornblende from Lüderitz, Namibia: mineral description and crystal chemistry. (16th May 2018) - Oberti, Roberta; Boiocchi, Massimo; Hawthorne, Frank C.; Ciriotti, Marco E.
ABSTRACT: Magnesio-hornblende (IMA2017-059) has been characterized in a specimen collected in the sand dunes of Lüderitz, Karas Region, Namibia. The empirical formula derived from electron microprobe analysis and single-crystal structure refinement is A (□0.73 Na0.22 K0.05 )Σ1.00 B (Ca1.79 Fe 2+ 0.10 Mg0.04 Mn 2+ 0.03 Na0.04 )Σ2.00 C (Mg3.48 Fe 2+ 0.97 Al0.28 Fe 3+ 0.23 Cr 3+ 0.01 Ti0.03 )Σ5.00 T (Si7.18 Al0.82 )Σ8.00 O22 W [(OH)1.93 F0.05 Cl0.02 ]Σ2.00 . Magnesio-hornblende is biaxial (–), with α = 1.640(2), β = 1.654(2), γ = 1.666(2) (measured with gel-filtered Na light, λ = 589.9 nm), 2V (meas.) = 82(1)° and 2V (calc.) = 84.9°. The unit-cell parameters are a = 9.8308(7), b = 18.0659(11), c = 5.2968(4) Å, β = 104.771(6)° and V = 909.64 (11) Å 3 with Z = 2 and space group C 2/ m . The strongest eight reflections in the X-ray powder pattern [ d values (in Å), I, ( hkl )] are: 2.709, 100, (151); 8.412, 74, (110); 3.121, 73, (310); 2.541, 58, ( $\bar{2}$ 02); 3.386, 49, (131); 2.596, 45, (061); 2.338, 41, ( $\bar{3}$ 51); and 2.164, 39, (261).